The Communication Strategies to Avoid Conflicts When Speaking to Sasak Speakers: A Language Style Analysis - Sugianto; Tawali (Journal of Language and Literature Studies, 2024)
Sasak language is a language spoken by mostly whole people who live in Lombok Island, West Nusa Tenggara. As a main media of communication in Lombok, the possibility to get interact with them is wide open since Lombok had become a famous place stayed by various person from all around the world. For the sake of maintaining good relationship with people in Lombok who speak sasaknese, it is crucial to find out what kind of conflicts might happen when communicate to them. Therefore, here is the research aimed at uncovering the conflicts avoidances utilized by speakers of "Sasak," a language belonging to the Austronesian language family, when they converse in "Sasaknese." The study qualitatively describes how Sasak speakers maintain a good relationship and avoid getting involved into possible conflicts through language style and language used. To ensure the accuracy and validity of the data regarding Sasaknese conflict avoiding styles, some relevant literatures on pertinent issues was extensively reviewed to provide supporting data sources. Data collection and analysis followed three stages of analysis: data reduction, data display, and conclusion drawing and verification. Based on the result of analysis, the study showed that communication strategies applied by Sasak speakers include noble language, Commoner language, and conventional language. Noble language applied formal lexicon, intricate grammatical structures, and deferential speech patterns. The commoner language is used among ordinary people in everyday interactions, including among peers, friends, and family members. It is more casual and relaxed compared to noble language, with simpler vocabulary and grammar. Conventional language refers to rude language and is categorized as low status but it contibutes in avoiding conflict.